Performance and emission characteristics of waste frying oil biodiesel blends as pilot fuel on a dual fuel compression ignition engine - Aydin, Zafer; Safa, Aykut (TAYLOR & FRANCIS INC, 2025)
In recent years, diesel engine researchers have turned onto alternative fuel due to international emission legislations and depletion of fossil fuels. Natural gas and biofuels as an alternative fuel have gained popularity with simple and low-cost utilization in diesel engines. In the present study, effect of compressed natural gas (CNG) application with pilot injection of waste frying oil biodiesel (WFOB) blends have been investigated on performance and emissions of a diesel engine running under full load at 3000 rpm speed. Engine tests have been carried out according to ISO 8178 E2 test cycle, at maximum rated power for 0%, 20%, 40%, and 60% substitution ratios of CNG and 0%, 10%, 20% of WFOB content in pilot diesel fuel. It is found that, in dual fuel mode; ignition delay period is longer than the standard diesel operation, and in dual fuel mode; thermal efficiency is lower than the standard diesel operation. Moreover, a significant reduction is observed in nitrogen oxides (NOx) emission and smoke opacity with an increase of carbon monoxide (CO) and hydrocarbon (HC) emissions. With the use of pilot WFOB blends, ignition delay period becomes shorter. NOx emissions increase, while CO, HC emissions, and smoke opacity decrease.
Keywords: Diesel engine; emissions; dual fuel; compressed natural gas; waste frying oil biodiesel; METHYL-ESTER BLENDS; NATURAL-GAS; DIESEL-ENGINE; COMBUSTION CHARACTERISTICS; CI ENGINE; INJECTION; CNG; OPERATION; EGR; QUANTITY; Energy & Fuels; Engineering; Environmental Sciences & Ecology